Influence of Sensor Nodes on the Invulnerability of Tree Network - Lifeng Jiang; Fengming Zhang; Rennong Yang; Kun Xu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
In the transformation process from the complex system of great industrial era to the information era, the component having sensing function plays an important role in the evolution of complex system. To abstract the complex system of “tree” structure as “tree” network, To abstract the components include the component having sensing function as nodes, and how the sensor nodes in the network affect network invulnerability is studied quantitatively in this paper. Firstly, the experimental program for network invulnerability is designed; secondly, the indicators for measuring the network invulnerability and the importance of node are proposed; then, the invulnerability experiments are carried out in two conditions-with or without sensor nodes in “tree” network; finally the experimental data are statistically analyzed. Results show that after the addition of sensor nodes, the invulnerability of “tree” network is promoted when subject to random attack and particular attack. The research results are of reference significance for improving self-invulnerability in the transformation process from complex system to information. The experimental program and the relevant conclusions obtained by experiment in this paper have certain innovation.